Estimativa do torque de flexão plantar isométrica a partir de modelos musculares com e sem reflexos neuromusculares - Moura, Éder Alves de (2010)
This thesis is a proposal for evaluation of two different muscle models that, fed by electromyographic signals collected from gastrocnemius medialis, gastrocnemius lateralis, soleus and tibialis anterior in an experimental isometric plantar flexion torque for 20 and 60 percent of their maximum voluntary contraction, estimates the muscle torque for the same situation. The models differ by the structures that they represent. The first model is the work of Menegaldo (Menegaldo, 1997) which is a modification of the extrafusal fibers modeling proposed by Zajac (F E Zajac, 1989). The second proposition is based on Winters (Winters, 1995a; 1995b), which incorporates structures of the reflex system in the modeling of extrafusal fibers. The assessment of these two approaches showed that for the cases studied, the modified model of Zajac gives the best results, in general. However, there were indications that the representation of the reflex system is important in situations of low level of muscle activation. It was also noted that modeling the dynamics of muscle activation play a key role in accurate estimates of muscle torque and should be further investigated.